PEMETAAN POTENSI TANAMAN PANGAN MELALUI DIVERSIFIKASI PANGAN DI KABUPATEN OGAN KOMERING ULU - Ema Pusvita; Putri Ayu Ogari; Ahmad Iskandar (Jurnal Prodi Agribisnis, 2022)
Ogan Komering Ulu Regency has various types of food crops that can be used as a substitute forrice which is the staple food of its people. These types of food corn, cassava, sweet potatoes andsoybeans. This study aims to determine the potential of food crops in each sub distric in Ogan KomeringUlu district and determinane strategies to support food security. The mrthods used are quantitative andqualitative methods and the analytical methods used are LQ and Descriptive analysis. The data used arefrom 13 sub districts in the desert for 10 years (2010 – 2019). The results of this study are that there are 8sub districts that have the potential to develop corn commodities, 8 cassava sub districts, 9 sweetpotatoes sub districts and 5 soybean sub districts. And the strategy used is to increase food cropproduction, realize food crop agribusiness and improve marketing management.